Primary bone diffuse B cell lymphoma of the thoracic spine: a rare entity - Akçay, Emrah; Benek, Hüseyin Berk; Yılmaz, Hakan; Tabanlı, Alper; Yurt, Alaattin (The European Research Journal, 2023)
Primary bone lymphoma is a rare entity, accounting for approximately 3-7% of malignant bone tumors, 5% of extra-nodal lymphomas and <1% of all non-Hodgkin lymphomas. Primary spine localized lymphoma is 1.7% of all primary bone lymphomas. A 73 year-old female presented with a two month history of severe backache. T1W and T2W MRI showed a hypointense soft tissue component extending from the left posterior elements to Th7 corpus. The patient underwent Th6-7-8 total laminectomy. Th7-8 extradural mass was totally resected. Excisional biopsy was performed through Th7 left pedicle and vertebroplasty was applied. Significant reduction in pain was seen postoperatively. The patient was diagnosed with diffuse large B cell lymphoma. R-CHOP chemotherapy and local radiotherapy were applied. Any other lesions were not detected after the examinations following 6 months period and it was accepted as primary bone lymphoma.